PENGARUH KNOWLEDGE SHARING, MOTIVASI TERHADAP KINERJA DENGAN LEARNING ORGANIZATION SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Kader Desa Cabean Demak) - Sulistyorini, Sulistyorini; Octavia, Ayu Nurafni; Setyarini, Any (JURNAL ILMIAH EDUNOMIKA, 2023)
The higher the goal of optimal performance, the higher the obstacles to achieving this performance, so village cadres measure organizational performance by looking at the number of visits by the community, especially the routine activities of Posyandu toddlers and the elderly, seeing how active community visits have not reached the target. The performance of cadres in achieving the target of active visits still needs to be improved. This research aims to test the knowledge sharing variable, motivation, on the performance of cadres with learning organization as an intervening variable. This study uses a quantitative research approach. This research was conducted at Cabean Demak Village Cadres. The research population was all cadres with saturated sampling techniques; all people were sampled. The regression equation in this study is through 2 equations, namely the first equation Y1=0.339X1+0.610 X2 and Equation II Y2=0.331X1+0.293X2+0.376 Y1. So that it can be explained that the variable knowledge sharing, motivation has a positive and significant effect on learning organization and the variables of knowledge sharing, motivation and learning organization have a significant effect on the performance of cadres. In addition, the Sobel test shows that learning organization can mediate knowledge sharing and motivation on cadre performance. Keywords: knowledge sharing, motivation, learning organization, performance.